Study of the Effect of Mineral Components on the Permeability Impairment Rate and Stress Sensitivity Factor of Shale. (21st February 2022) - Wang, Shuang; Wu, Zhonghu; Chen, Jun; Liu, Hao; Wang, Ruyue; Liu, Jingshou
Abstract : The mineral components play an indispensable role in shale reservoirs, and the study of their content and character are significant for the permeability impairment rate and stress sensitivity of shale reservoirs. In this study, the shale cores from the FC1 well of the Lower Cambrian Niutitang Formation in northern Guizhou were used to analyze the mineralogical composition of five samples using X-ray diffractometry and for measurement of permeability and porosity of samples by means of the FYKS-2 high-temperature overburden porosimeter with N2, and the samples were also subjected to uniaxial compression tests using the INSTRON 1346 electrohydraulic servo-controlled material testing machine (200T), thereby analyzing the effect of mineral components on the permeability impairment rate and stress sensitivity coefficient of shale. Results indicate that the permeability and porosity are negatively correlated with effective stress and clay mineral content, and positively correlated with detrital mineral content, whereas, the change of mineral composition is not obvious for porosity. Simultaneously, the permeability impairment rate and stress sensitivity factor decrease with growing quartz content and modulus of elasticity, and increase with rising clay mineral content. Additionally, the greater the brittle minerals content of shale, the more likely it is to undergo brittle damage and more crack extension during compression with predominantly elastic deformation, resulting in a lower stress sensitivity factor. Conversely, the higher is the stress sensitivity factor. The research results further deepen the understanding of mineral components on the permeability and mechanical properties of shale reservoirs.